PENERAPAN DATA MINING PADA PENJUALAN MAKANAN DAN MINUMAN MENGGUNAKAN METODE ALGORITMA NAÏVE BAYES: Studi Kasus : Makan Barbeque Sepuasnya - Fauzan Alghifari; Didi Juardi (Teknik Informatika, 2021)
Changes in human behavior against the times, this causes business actors, especially culinary businesses to innovate so that the business they run continues to survive. With this competence, it causes more problems, one of which is the emergence of startups that eventually become competitors in the business world in all fields. All business owners have an innovation by analyzing food and beverage sales to generate new opportunities which will then be used to identify future opportunities. This affects the income and expenses obtained by companies and restaurants. This research paper generates new knowledge, namely by using the Na Bayve Bayes algorithm to generate an opportunity in the sale of food and beverages based on sales in the previous month. The results of the analysis process will be used for the benefit of restaurants in marketing optimization efforts. This new knowledge will also provide information such as the results of sales opportunities in the following months